Translating Delirium Prevention Strategies for Elderly Adults with Hip Fracture into Routine Clinical Care: A Pragmatic Clinical Trial. Issue 3 (22nd November 2016) - Freter, Susan; Koller, Katalin; Dunbar, Michael; MacKnight, Chris; Rockwood, Kenneth
Abstract : Objectives: To compare the feasibility (adherence) and effectiveness (prevalence of delirium, length of stay, mortality, discharge site) of delirium‐friendly preprinted postoperative orders (PPOs) for individuals with hip fracture, administered by regular orthopedic nurses, with routine postoperative orders. Design: Pragmatic clinical trial to evaluate a quality improvement intervention. Setting: Tertiary care hospital. Participants: Individuals aged 65 and older admitted for hip fracture repair (N = 283). Intervention: PPOs with delirium‐friendly options and doses for nighttime sedation, analgesia, and nausea and attention to catheter removal and bowel movements. Measurements: Adherence to PPO was compared with adherence to routine orders. Drug doses were recorded. Presence of delirium was documented using the Confusion Assessment Method and the Mini‐Mental State Examination on postoperative Days 1, 3, and 5. Length of stay, discharge site, and in‐hospital mortality were recorded. Results: Orthopedic nurses adhered reasonably well with delirium‐friendly PPOs. Of 283 participants, 42% developed postoperative delirium, with significantly less delirium in the intervention group (intervention 33%, control 51%, P = .001). The effect of the intervention was stronger in individuals with preexisting dementia (intervention 60%, control 97%, P < .001). Participants with postoperative delirium had longer hospital stays and were more likely to die or be discharged to a nursing home, but there was no significant between‐group difference in these outcomes. Conclusion: It is possible to introduce delirium‐friendly PPOs into routine post‐hip fracture care in a representative elderly population including individuals with dementia. Delirium‐friendly PPOs executed by regular nursing staff resulted in a significant reduction in postoperative delirium but no difference in other outcomes.